Early and current physical activity: relationship with intima-media thickness and metabolic variables in adulthood - Lima, Manoel C. S. [UNESP]; Barbosa, Maurício F.; Diniz, Tiego A. [UNESP]; Codogno, Jamile S. [UNESP]; Freitas Júnior, Ismael F. [UNESP]; Fernandes, Rômulo A. [UNESP] (Associação Brasileira de Pesquisa e Pós-Graduação em Fisioterapia, 2014)
Background:It is unclear whether early physical activity has a greater influence on intima-media thickness and metabolic variables than current physical activity.Objective: To analyze the relationship between current and early physical activity, metabolic variables, and intima-media thickness measures in adults.Method: The sample was composed of 55 healthy subjects of both sexes (33 men and 22 women). Total body fat and trunk fat were estimated by dual-energy X-ray absorptiometry. Carotid and femoral intima-media thickness were measured using a Doppler ultrasound device. A 12-hour fasting blood sample collection was taken (fasting glucose and lipid profile). Early physical activity was assessed through face-to-face interview, and the current physical activity was assessed by pedometer (Digi-Walker Yamax, SW200), which was used for a period of seven days.Results: Current physical activity was negatively related to total cholesterol (rho=-0.31), while early physical activity was negatively related to triglycerides (rho=-0.42), total cholesterol (rho=-0.28), very low density lipoprotein (rho=-0.44), and carotid intima-media thickness (rho=-0.50). In the multivariate model, subjects engaged in sports activities during early life had lower values of very low density lipoprotein (b=-8.74 [b=-16.1; -1.47]) and carotid intima-media thickness (b=-0.17 [95%CI: -0.28; -0.05]).Conclusion: Early 95%CI physical activity has a significant influence on carotid intima-media thickness, regardless of the current physical activity.
Keywords: maintenance of physical activity; physical activity; atherosclerosis; insulin resistance; movement